The contralateral limb is no reliable reference to restore coronal alignment in TKA - Beckers, Lucas; Colyn, William; Bellemans, Johan; Victor, Jan; Vandekerckhove, Pieter-Jan (Knee surgery, sports traumatology, arthroscopy : official journal of the ESSKA, 2022)
Purpose Implementation of morphometric reference data from the contralateral, unaffected lower limb is suggested when reconstructing the coronal plane alignment in TKA. Limited information, however, is available which confirms this left-to-right symmetry in coronal alignment based upon radiographs. The purpose of the study was, therefore, (1) to verify if a left-to-right symmetry is present and (2) to assess whether the contralateral lower limb would be a reliable reference for reconstructing the frontal plane alignment. Methods Full-leg standing radiographs of 250 volunteers (male, 125; female,125) were reviewed for three alignment parameters (Hip–Knee–Ankle angle (HKA), Femoral Mechanical Angle (FMA) and Tibial Mechanical Angle (TMA)). Evaluation of assumed left-to-right symmetry was performed according to two coronal alignment classifications (HKA subdivisions (HKA) and limb, femoral and tibial phenotypes (HKA, FMA and TMA)). Inter- and within-subject variability was calculated, along with correlations coefficients ( r ) and coefficients of determination ( r 2 ). Reliability of the contralateral limb as a personalized reference to reconstruct the constitutional alignment was investigated by intervals, expanding by 1° increments (0.5° increment both to varus and valgus) around the right knee alignment parameters. Subsequently, it was verified whether or not the left knee parameters fell within this interval. Results Symmetrical distribution in coronal alignment was found in 79% (HKA subdivision) and 59% (limb phenotype) of the cohort. Gender differences were present for the most common symmetric limb phenotypes (VAR HKA 3° (23.2%) in males and NEU HKA 0° (38.4%) in females). Inter-subject variability was more prominent than the within-subject side differences for all parameters. Correlations analyses revealed mostly moderate correlations between the alignment measurements. Coefficients of determination showed overall weak left-to-right relationship, except for a moderate predictability for HKA ( r 2 = 0.538, p < 0.001) and FMA ( r 2 = 0.618, p < 0.001) in females. FMA and TMA marked weak predictive values for contralateral HKA. Only 60% of left knees were referenced within a 3° interval around the right knee. Conclusion No strict left-to-right symmetry was observed in coronal alignment measurements. There is insufficient left-to-right agreement to consider the concept of the contralateral unaffected limb as an idealized reference for frontal plane alignment reconstruction based upon full-leg standing radiographs. Level of evidence I.